Formulation of an instantly dissolvable solid eye drop device for topical ocular delivery - Moosa, Raeesa Mahomed (My University, 2014)
Ocular diseases of the anterior segment are ubiquitous, especially among elderly patients. The development of novel drug delivery systems on the journey for improved treatment is therefore imperative. Aside from anatomical and physiological barriers of the eye, the actual dosage form plays a crucial role. Although liquid eye drops are the first-choice dosage form, the shortcomings do not go unnoticed. In an attempt to circumvent these drawbacks, a novel instantly soluble eye drop device was developed. The system aimed to provide an easier administration form, comfort for the patient and improve drug bioavailability to anterior chamber. This was a steer toward attaining patient-convenience and compliance which are critically challenging factors. Preformulatory studies allowed for the screening and selection of candidate components and key processing conditions. Hydrophilic polymers and excipients were selected for attainment of small, rapid disintegrating yet robust matrices via lyophilization of solutions. Design of experiments generated formulations by means of a Face centred central composite design (FCCCD) that underwent thorough physicochemical and mechanical assessment. Overall, robust rapidly disintegrating solid eye drops were produced. Fastest disintegration time was noted to be 0.200s. Drug content ranged from 79-96%. An improved permeation of formulations compared to a pure drug dispersion was seen. Mathematical modeling was conducted for better insight into the behavior of the device on the eye surface. Statistical analysis through constraint optimization yielded a single optimal formulation. Thermal and molecular transition analysis showed congruent findings with no incompatibility between components. Combinatory surface morphology and porositometric studies confirmed the presence of interconnecting pores across the matrix surface. Drug release kinetic evaluation predicted that best model fit was first-order release. Ocular irritancy studies by means of the HET-CAM test indicated that both drug-loaded and drug-free eye drops had an irritation score of 0 with the inference of good tolerability. Ex vivo permeation across excised rabbit cornea showed an improved steady state drug flux (0.00052mg.cm-2.min-1) and permeability co-efficient (1.7x10-4cm.min-1) for the optimized device compared to pure drug and a marketed eye drop preparation. In vivo analysis was conducted on the rabbit model with insertion of the device into the ocular cul-de-sac. Subsequently, ultra performance liquid chromatography (UPLC) analysis of the aspirated aqueous humour for model drug timolol maleate detection was conducted. The device demonstrated improved drug levels (Cmax = 3ug/mL) in comparison to commercial eye drops (Cmax = 1.97ug/mL) and was well tolerated. Level A point-to-point IVIVC plots indicated a R2 value of 0.84. This served to imply that the in vitro dissolution data can be compared to and may serve as a surrogate to that of in vivo pK data. Histopathological assessment on the enucleated eye ball confirmed the lack of noxious effects of the device on ocular tissue. From this study, the solid eye drop device was concluded to be safe as a drug delivery system for the anterior eye. Looking toward innovative trends and modifications, a bi-layered solid eye drop system with enhanced permeability capabilities employing low molecular weight chitosan was further fabricated for preliminary investigation.
Thesis (M. Pharm.)--University of the Witwatersrand, Faculty of Health Sciences, 2013.
Keywords: Eye Diseases--drug therapy; Drug Delivery Systems